Movies and moral dilemma discussions : a practical guide to cinema based character development - Waters, Stewart; Russell, William B. (Teaching and learning social studies., 2020)
"Movies and Moral Dilemma Discussions: A Practical Guide to Cinema Based Character Development explores the values, attitudes, and beliefs depicted on film. Since the beginning of the film industry movie makers have depicted morals and values on the silver screen. Teachers will find the book to be a valuable guide for infusing character education and film into the classroom. The book includes an overview of character education, a discussion of film pedagogy, and explores utilizing film for educational purposes"--